CTNI-57. LOW-RISK MENINGIOMA: OUTCOMES FROM NRG ONCOLOGY/RTOG 0539. (9th November 2020) - Rogers, Leland; Pugh, Stephanie; Vogelbaum, Michael; Perry, Arie; Ashby, Lynn; Modi, Jignesh; Alleman, Anthony; Youssef, Emad; Braunstein, Steve; Bovi, Joseph; de Groot, John; Whitton, Anthony; et al.
Abstract: PURPOSE/OBJECTIVE(S): Outcomes of low-risk meningioma from NRG/RTOG-0539. MATERIALS/METHODS: Outcomes of the intermediate and high-risk cohorts from this phase II trial have been previously reported. Low-risk (Group 1: new WHO grade 1) patients were observed after gross total (GTR) or subtotal resection (STR). Progression-free (PFS) and overall (OS) were estimated using Kaplan-Meier. CTCAE v3 AE grading was employed. RESULTS: Group 1 enrolled 65 patients. 56/60 (93.4%) evaluable patients had investigator-reported GTR. Sufficient imaging for central confirmation was available for 48: GTR in 35 and STR in 13. Median follow-up for living patients was 9.1 years (y). For all evaluable patients 5 and 10 y PFS and OS rates were 89.4 and 85.0%, and 98.3 and 93.8%, respectively. For patients with centrally-confirmed STR, 5/10 y PFS rates were 72.7/72.7%, with 100% 10 y OS. For patients with centrally-confirmed GTR, 5/10 y PFS and OS rates were 94.3/87.6 and 97.1/90.4%, respectively. For combined study cohorts (Groups 1–3) with central-review (n=104), the median centrally-measured largest pre-operative tumor dimension was 4.3 cm (range 0.4 - 14.4); this was significantly associated with OS (hazard ratio [HR]=1.03, p=0.021) and PFS (HR=1.03, p=0.003). No grade 4 or 5 protocol-related adverse events were reported. There were 1 grade 3 (infection), 4 grade 2 (neurologic, pulmonary, gastrointestinal, and pain), and 5 grade 1 (3 neurologic, 1 occulovisual, 1 constitutional) events from 5 patients. CONCLUSION: These results prospectively validate high OS and PFS outcomes for low-risk meningioma managed with surgery followed by observation, but raise questions regarding optimal management following STR (5 y PFS 72.7%), a subcohort that could potentially benefit from adjuvant therapy. However, we identified considerable discordance between local and central assessments of resection extent. Pre-operative tumor size has a significant impact on OS and PFS. Supported by: U10CA180868 and U10CA180822 from the National Cancer Institute (NCI)